Prognostic value of pretreatment anemia in patients with diffuse large B-cell lymphoma treated with R-CHOP - Nguyen, Thi Thuy; Nguyen, Thi Linh; Phan, Minh Tri; Phan, Thi Do Quyen (Tạp chí Y Dược Huế, 2026)
ABSTRACT Background: Diffuse Large B-Cell Lymphoma (DLBCL) is the most common subtype of non-Hodgkin lymphoma. While R-CHOP is the standard of care, treatment failure remains a challenge. Pretreatment anemia is a common paraneoplastic manifestation, yet its prognostic utility in Vietnamese patients remains under-investigated. Materials and Methods: A combined prospective and retrospective study was conducted on 106 patients with CD20-positive DLBCL treated with first-line R-CHOP at Hue University of Medicine and Pharmacy Hospital, Hue Central Hospital and Da Nang Oncology Hospital from December 2022 to August 2025. Pretreatment anemia was classified according to NCI-CTCAE v5.0. Clinicopathological features, toxicity, treatment response, and survival were analyzed. Results: The prevalence of pretreatment anemia was 32.1%, with the majority being Grade 1 (26.4%). Anemia was significantly associated with B symptoms (p=0.034) and older age (p=0.039). Regarding efficacy, non-anemic patients had approximately 12 times higher odds of responding (Odds Ratios = 11.897; 95% CI: 1.33–106.34, p = 0.014). Toxicity analysis showed a 3.8% treatment-related mortality rate due to severe infections. There was no statistically significant difference in overall survival or progression-free survival (p > 0.05). Conclusion: Pretreatment anemia is a robust and easily accessible predictor of poor early treatment response in Vietnamese patients with DLBCL treated with R-CHOP. Anemic patients have significantly lower odds of achieving remission. While long-term survival benefits were obscured by treatment-related toxicity in this cohort, the strong link between hemoglobin levels and therapeutic efficacy suggests that anemia should be integrated into risk stratification.